Traditionalister och radikala i efterkrigstidstidens svenska musikliv: kring Jan Carlstedt och hans stråkkvartett nr 2 - Berglund, Lars (Svensk tidskrift för musikforskning / Swedish Journal of Music Research, 2009)
During the 1950s and early 1960, the art music scene in Sweden saw a conflict between the advocates of a more traditionalist and moderate modernism on the one hand, and the devotees of radical and experimental music on the other. The most articulate spokesman for the traditionalist camp was the composer Jan Carlstedt (1926–2004), a pupil of Lars Erik Larsson. In my article this historical tension between traditionalists and radicals is analysed using material from newspapers, magazines and not the least the diary of Bo Wallner, a source which gives unique insights in the silent play behind the scenes. It is argued that the opposing fractions to a large extent shared similar aesthetic views, and that the conflicts of opinion was a matter of style rather than fundamental aestetic questions. Moreover the schism was a result of conflicting agendas of a more musico-political kind, the radical camp working to strengthen the position of Swedish music on the international arena. Therafter Jan Carlstedts music aesthetic stance is scrutinized, via his statements about his own music as well as that of his models – especially Sergei Prokofiev and Dmitry Shostakovic. Moreover the practical, compositional consequences of that stance are exemplified through an analysis of his second string quartet (1966), which he himself pointed out as a key work. The ambition to regenerate art music by “giving new meaning to the lasting elements of the musical tradition” turns out to be a central idea in Carlstedt's views on music. In the second quartet this is mainly attempted by unconventional manipulations of a basically traditional harmonical language, taking inspiration from the music by Shostakovic, Bartók and Britten. In this process, he often used different kinds of symmetrical patterning. The harmonic language can at times be quite dissonant, but this is balanced with quite conventional schemes of melody, rhythm and phrase organisation. His musical language is related to that of Shostakovic, but lacks the Russians complex stylistic fractures.